An Analysis of the Role of Godparents in Supporting Children’s Faith Formation at Saint Joseph Parish, Gedangan - Alfrida Dogomo; Gregorius Daru Wijoyoko; Nerita Setiyaningtyas; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to analyze the role of godparents in accompanying the faith development of children at Saint Joseph Parish Gedangan, Semarang. The role of godparents is not merely symbolic during the baptismal ceremony, but also entails an ongoing responsibility to guide children toward maturity in faith. This research employs a qualitative approach with a case study design involving ten informants, consisting of the parish priest, catechists, godparents, and baptized children. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic analysis methods. The findings indicate that the understanding and implementation of the godparents’ role develop in accordance with experience and social context. Godparents function as spiritual companions, role models of lived faith, and part of the child’s faith support system. Geographical distance and social mobility emerged as major challenges affecting the effectiveness of accompaniment. These findings emphasize the need for continuous formation for godparents, their integration into the parish pastoral system, and close collaboration between godparents, parents, and catechists. This study contributes theoretically to the development of studies on the sacraments of initiation and offers practical contributions for the Church in strengthening pastoral models of children’s faith accompaniment.